Larva-relevant genes expression in embryonic development stages of domesticated silkworm (Bombyx mori L.) - 陈金娥; YANG Hui-juan; LI Jian-ying; SHEN Yan-wei; ZHONG Bo-xiong (浙江大学学报. 农业与生命科学版)
Gene expression in embryonic stages of silkworm was investigated through analysis of protein expression profile. Proteins from embryonic stages were separated by using two-dimensional electrophoresis (2-DE). The 2-DE images were analyzed using software ImageMaster Elite. Some spots with high abundance would express throughout the following specific stages once they were detected. These proteins may play an important role in embryonic development and metabolism. 5 spots of them were excised from the gels and analyzed their sequences and function. These sequences were identified by using matrix-assisted laser desorption ionization- time of flight mass spectrometry (MALDI-TOF-MS). It is found that five larval functional proteins were expressed in four embryonic stages after homology searching based on peptide mass fingerprinting MS results against related database, that is, juvenile hormone binding protein presented in shortening stage, epidermal growth factor receptor presented in head thorax differentiation stage, larval cuticle protein and accessory gland specific peptide presented in tubercle stage, amylase presented in body pigmentation stage. These functional proteins are seen to express in certain stages for preparing to meet the certain physiological demands, which suggest the larvae relevant genes have been expressed orderly and timely in embryonic stages.